Photodynamic Therapy: A Rising Star in Pharmaceutical Applications - Eduard Preis; Udo Bakowsky (MDPI AG, 2024)
The interest in photodynamic therapy (PDT) has increased remarkably over the past years, with over 75% of all related articles published after 2010 (Figure 1) [...]